2012
DOI: 10.1073/pnas.1211803109
|View full text |Cite
|
Sign up to set email alerts
|

G9a functions as a molecular scaffold for assembly of transcriptional coactivators on a subset of Glucocorticoid Receptor target genes

Abstract: Histone H3 lysine-9 methyltransferase G9a/EHMT2/KMT1C is a key corepressor of gene expression. However, activation of a limited number of genes by G9a (independent of its catalytic activity) has also been observed, although the precise molecular mechanisms are unknown. By using RNAi in combination with gene expression microarray analysis, we found that G9a functions as a positive and a negative transcriptional coregulator for discrete subsets of genes that are regulated by the hormone-activated Glucocorticoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 43 publications
7
131
0
Order By: Relevance
“…Second, Hic-5 depletion had dramatic effects on Dexregulated transcription of some genes, in which Hic-5 served as an all-or-none switch, so that Dex-induced transcriptional regulation by GR was completely dependent on the presence of Hic-5 for some genes and on the absence of Hic-5 for other genes. In contrast, depletion studies with many other coregulators have indicated that they serve as modulators rather than as all-or-none determinants of steroid hormone-regulated gene expression (2,(36)(37)(38)(39). Third, Hic-5 was able to function as a coactivator and as a corepressor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, Hic-5 depletion had dramatic effects on Dexregulated transcription of some genes, in which Hic-5 served as an all-or-none switch, so that Dex-induced transcriptional regulation by GR was completely dependent on the presence of Hic-5 for some genes and on the absence of Hic-5 for other genes. In contrast, depletion studies with many other coregulators have indicated that they serve as modulators rather than as all-or-none determinants of steroid hormone-regulated gene expression (2,(36)(37)(38)(39). Third, Hic-5 was able to function as a coactivator and as a corepressor.…”
Section: Discussionmentioning
confidence: 95%
“…Current evidence suggests that scores of coregulators cooperate in the transcriptional regulation of each gene, with each coregulator contributing a specific molecular function, e.g., remodeling of chromatin or transcription complex assembly/disassembly (1). Moreover, coregulators act gene specifically, using different activation and repression domains to perform different actions on different genes, as specified by the bound GR (2)(3)(4)(5)(6). Protein allostery and the combinatorial nature of transcriptional regulation are responsible for the gene specificity of receptor and coregulator function (7,8), but the specific steps facilitated by a coregulator in a given context are mostly unknown.…”
mentioning
confidence: 99%
“…45 Ehmt2 has been shown to be essential for activation of several genes critical to early development including p21 46 and b-Globin. 47 Unlike transcriptional repression, Ehmt2's co-activator role does not require either the SET or Ank repeat domains, 6,46,48 suggesting that this coactivator role is methylation-independent. Furthermore, Ehmt2 is dependent upon a different pool of transcription factors, such as Runx2 49 and Nfe2, 47 to recruit it to sites of transcriptional activation.…”
Section: Methylation-independent Transcriptional Activating Functionsmentioning
confidence: 99%
“…Furthermore, Ehmt2 is dependent upon a different pool of transcription factors, such as Runx2 49 and Nfe2, 47 to recruit it to sites of transcriptional activation. Once recruited Ehmt2 in turn functions as a scaffold protein to enhance recruitment of further co-activators including Carm1, 45 p300, 48 the mediator complex 14 and DNA Pol II. 47 In contrast, Ehmt1 has also been recently implicated in transcriptional activation during adipogenesis independent of Ehmt2.…”
Section: Methylation-independent Transcriptional Activating Functionsmentioning
confidence: 99%
“…In this respect, G9a was recently reported as a transcriptional coactivator for Glucocorticoid Receptor (GR), by forming a molecular scaffold to recruit and facilitate binding of other co-activating proteins including GRIP1, CARM1 and p300 32,34 . Interestingly, the underlying mechanism of G9a function as a positive regulator is methylation-independent, because UNC0646 (G9a-specific methyltransferase inhibitor) can not abolish this feature 34 , 30 .…”
mentioning
confidence: 99%